THE INGENUITY OF THE TONAL PLAN OF THE DEVELOPMENT SECTIONS OF THE SONATA FORMS OF PIANO SONATAS BY W. A. MOZART - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
I have to admit that, when I intended to write this study, I still had to analyze harmonically and tonally the development sections of the Mozart forms of the sonata of the Piano Sonatas. Only after I have put the title I thought of the fact that I might had jumped to conclusions with this title. I opened the Explanatory Dictionary of the Romanian Language to look for ingenuity in order to fins out the explanation for myself. “Ingenuity. 1. The one who has a lot of inventive spirit, the one that is intelligent, resourceful, knows how to do things. 2. Made, manufactured inventively, skilfully, wisely. ”I was thinking that, is it possible for Mozart to have these qualities in the development sections of his sonatas? Are they made inventively, skilfully and wisely? Moreover, if it is so, how do they become real?